What Happens When Food Marketers Require Restrictive Farming Practices?. (25th May 2015) - Saitone, Tina L.; Sexton, Richard J.; Sumner, Daniel A.
Abstract : The dimensions that define a food product have expanded rapidly to include characteristics of the production process, marketing arrangements, and implications that production and consumption of the product have for the environment. Some market intermediaries have responded by requiring that their suppliers abide by restrictive production practices. We examine the economic effects of such restrictions and apply this analysis to limitations on the use of antibiotics in U.S. pork production. Results from conceptual and simulation analyses show that, in the absence of demand growth, less pork is sold due to higher costs in the restricted segment, and both pork consumers (on average) and producers are harmed. Demand growth of between 6–11% from adding new consumers who will consume the restricted (antibiotic‐free) product but not the conventional product is needed to return consumer surplus to the level in the base case, and between 2–4% demand growth was required to return producer surplus to base. When restricted and conventional products are modeled using a vertical differentiation framework, results depend importantly on the ease with which consumers can switch to a seller who offers their desired product type. Significant distributional impacts among consumers are present when switching costs are prohibitive.